Babassu mesocarp (Orbignya pharelata Mart.) supplementation decreased markers of muscle damage, pain, and perceived exertion in trained young futsal athletes - Crislane de Moura Moura; Valmir Oliveira Silvino; Victor Hugo de Freitas; Teresa Cristina do Nascimento Salazar; Rayane Carvalho de Moura; Sévulo Fernando Costa Lima; Tiago Ribeiro Patrício; Alexandre Sérgio Silva; Marcos Antonio Pereira dos Santos (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Introduction and objective: This study aimed to evaluate the efficacy of babassu mesocarp flour (Orbignya pharelata Mart.) supplementation on muscle damage, pain, and effort perception in futsal athletes. Materials and methods: This is a randomized, single-blind, placebo-controlled trial. Ten recreational futsal athletes consumed water, maltodextrin, and babassu mesocarp flour supplement in three different occasions before the training protocol. There was a 5-day washout period between sessions. Afterwards, they underwent a plyometric training session and the futsal-specific intermittent shuttle protocol test (FISP). Blood samples were collected for creatine kinase (CK) analysis. Results: There was a significant increase in CK levels after the babassu supplementation of 11.25% (p=0.02, d=0.26), whereas the Maltodextrin had a non-significant increase of 29% (p=0.08). The reported muscle soreness was smaller after the ingestion of babassu for the jump and FISP tests (p=0.03 e p=0.01, respectively) compared to water intake. No significant difference was found between Babassu and Maltodextrin intake regarding muscle soreness. Conclusion: Babassu mesocarp flour supplementation reduced biomarkers of muscle damage and effort perceptions. However, there was a greater decrease in CK levels after maltodextrin intake compared to babassu mesocarp flour supplementation.